A new type of familial partial lipodystrophy: distinctive fat distribution and proteinuria. (2nd October 2018) - Yurekli, Banu; Ozdemir Kutbay, Nilufer; Altay, Canan; Unlu, Sadiye Mehtat; Sen, Sait; Onay, Huseyin; Atik, Tahir; Akinci, Baris
ABSTRACT: Purpose : To describe an interesting subtype of familial partial lipodystrophy (FPLD). Methods : The phenotype of this distinctive FPLD subtype was studied in three Turkish female siblings. Results : Mutation testing was negative for the genes associated with lipodystrophy syndromes. In MRI studies, fat loss was prominent in the posterior aspects of the proximal lower limbs, whilst some fat was preserved in the anterior, medial and lateral aspects. Remarkably, fat tissue was preserved in the distal part of the limbs. Local fat accumulation was observed in the mons pubis area. Asymmetrical fat loss was also remarkable in the upper extremities. All three patients had severe insulin resistance associated with diabetes mellitus, acanthosis nigricans, hypertriglyceridemia and hepatic steatosis. Abnormal amounts of proteinuria were detected in all three subjects. Renal biopsy showed mild tubular atrophy, interstitial fibrosis, irregular thickening and wrinkling of glomerular basal membranes, small areas of segmental sclerosis and pedicel effacement. Conclusions : We reported a form of FPLD characterized by a striking pattern of highly selective partial fat loss and proteinuria.